Electrical impedance tomography reveals regional lung dysfunction in adults with preserved ratio impaired spirometry: an observational cross-sectional study - Zhang, Junsong; Qu, Shuoyao; Kong, Mingyi; Han, Liang; Ti, Xinyu; Zhao, Zhanqi (Frontiers in Medicine, 2025)
ObjectivePreserved ratio impaired spirometry (PRISm) is a condition characterized by abnormal spirometry results despite a normal forced expiratory volume in the first second (FEV1)/forced vital capacity (FVC) ratio. We hypothesized that electrical impedance tomography (EIT) would detect regional decreases in lung function in subjects with PRISm. The study aimed to explore the regional lung function differences between subjects with preserved ratio impaired spirometry (PRISm) and healthy volunteers.MethodsIn this observational study, subjects with respiratory symptoms visiting Xijing Hospital in May 2024 were rescreened for eligibility. Subjects meeting the PRISm criteria were included in the study. Electrical impedance tomography (EIT) and spirometry were conducted simultaneously. The same number of healthy subjects were studied, matching the gender, height, and weight in frequency. The regional lung function parameters were compared. A P-value of < 0.05 was considered statistically significant.ResultsA total of 16 subjects with PRISm, and 16 healthy volunteers were included in the study and evaluated. Functional EIT images provided information about the location of the dysfunctional lung regions. All evaluated EIT-based parameters were worse in the subjects with PRISm. Statistically significant differences were found in the regional obstructive ratio (rOR) and the median of the regional time constant τmed (p < 0.05). EIT-based parameters did not correlate with spirometry-based parameters, except for spirometry FEV1/FVC, which showed correlations with rOR (r = −0.53, p = 0.03) and τmed (r = −0.62, p = 0.01) in subjects with PRISm. Both τmed and rOR values were quite low in healthy volunteers, whereas substantial changes were observed in subjects with PRISm.ConclusionEIT-based regional lung function provides additional information to traditional spirometry, which visualizes and localizes regional lung function defects.